The Relationship Of Adolescent Women's Knowledge About Vulva Hygiene To The Occurence Of Leucorrhoea In The Environment Iii New Kelurahan Bambuo Medan Tuntungan District - Desi Anggraini (Institute of Computer Science (IOCS), 2019)
Vaginal discharge is a problem that most women complain about. Besides being very disturbing, vaginal discharge also has many influences, both on health and harmony. Vaginal discharge is not always a disease because there is also a normal vaginal discharge. The research method used is analytic observational with a cross sectional approach. The population in this study were all young women in Environment III Kelurahan Baru Ladang Bambu as many as 125 people. The sample is 56 people, with simple random sampling technique. The results showed that 91.1% had vaginal discharge, and 8.9% had no vaginal discharge. Of the 10 young women who had good knowledge the majority experienced vaginal discharge 100%, of the 30 young women who had sufficient knowledge the majority experienced vaginal discharge 86, 7% and out of 16 young women who had less knowledge, the majority experienced vaginal discharge, 93.8%. Obtained p value = 0.399 where p value 0.05. So it can be concluded that there is no relationship between the knowledge of adolescent girls about vulvar hygiene with the occurrence of vaginal discharge. It is hoped that health workers will provide counseling about reproductive health so that young women's knowledge about reproductive health is increasing, especially about vulvar hygiene and vaginal discharge.